Synthesis, characterization, biological evaluation, ADMET, and molecular docking studies of novel chalcone-sulfonate hybrid compounds as potential antioxidant and antiobesity activities - Korkmaz, Adem; Bursal, Ercan (Elsevier, 2025)
A novel series of methoxy substituted chalcone-sulfonate hybrid compounds were synthesized and characterized with 1H NMR, 13C NMR, and HRMS spectra analyses. The novel methoxy substituted chalcone-sulfonate hybrid derivatives (4a-n) were examined for their in vitro and in silico pancreatic lipase inhibition activities to see the possible antiobesity features. Among the novel chalcone-sulfonate derivatives, the compounds 4d (0.352 + 0.09), 4h (0.382 + 0.12), and 4a (0.405+0.34) were observed to be the more effective pancreatic lipase inhibitor from their lower IC50 values. Also, FRAP, CUPRAC and ABTS in vitro methods were showed the moderate antioxidant activities of the related compounds. Compounds 4 g, 4f, and 4m demonstrated significantly greater radical scavenging antioxidant activity compared to the other compounds in the ABTS radical scavenging assay, while compound 4f exhibited superior performance in the CUPRAC assay, and compound 4j showed the most pronounced effect in the FRAP assay. Moreover, molecular docking interactions and physicochemical, biochemical, and drug similarity properties of the compounds were performed utilizing some computational programs. In silico studies showed efficient biochemical properties and molecular interaction energy affinities of the compounds 4a and 4d compare to the orlistat, an approved obesity drug. In conclusion, the novel chalconesulfonate hybrid compounds (4a-n) exhibited good antioxidant and pancreatic lipase inhibitory properties, thus the pharmacological potential of these compounds can be supported by further studies.
Keywords: Chalcone-sulfonate hybrid; Pancreatic lipase; Enzyme inhibitions; Antioxidant; Molecular docking